Adaptability and phenotypic stability in guarana clones - Filho, Firmino José do Nascimento; Atroch, Andre Luiz; Cruz, Cosme Damião; Carneiro, Pedro Crescêncio Souza (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to determine parameters of adaptability and phenotypic stability of guarana clones (Paullinia cupana) in the state of Amazonas, Brazil. Ten trials were carried out in three counties, where 27 preselected guarana clones were evaluated in a four-year period. A randomized complete block design with two replicates were used, with plots formed by three plants spaced at 5x5 m. Four methods of adaptability and stability were evaluated. The nonparametric method of Lin & Binns modified showed satisfactory results and discriminated the clones performance both in favorable and unfavorable environments, and according to their stability levels. The CMU871 had good adaptability and high phenotypic stability. The CMU619 and CMU609 had specific adaptability to favorable and unfavorable environments, respectively.